Pengembangan Aplikasi MADU-E Pembelajaran Interaktif pada Materi PAI Bidang Ekonomi Kelas IV SD - Tsuraya Syaripudin (Awwaliyah: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2026)
This study aims to explain the strategies of Prophet Muhammad SAW in developing the economy of Medina as learning material for 4th-grade Islamic History (SKI). The main issue discussed is how the Prophet transformed the economic condition of Medina's society from poverty to self-sufficiency. This research is positioned as the development of relevant teaching materials for primary school students. The method used is a literature study with a historical approach. The results show that Prophet Muhammad built the economy through three main steps: constructing the Nabawi Mosque as a coordination center, fostering brotherhood between the Muhajirin and Ansar in economic cooperation, and establishing a fair Muslim market. Through this material, 4th-grade students are expected to understand the values of independence, honesty, and mutual cooperation in economic activities from an early age.